Bioprocess development: extraction and purification of human serum albumin from transgenic rice - Sheshukova, Kseniya Alekseyevna (Kansas State University, 2019)
Transgenic plant systems have successfully been used to express recombinant proteins, including rice seed-expressed recombinant human serum albumin (rHSA). The development of an efficient and integrated rHSA extraction and purification process would allow rHSA to be used for various medical applications such as replacing lost fluid and restoring blood volume, modulating inflammatory reactions, stabilizing vaccines, as well as treatment for cirrhosis, ascites, acute respiratory distress syndrome, etc., without risk of contamination of human pathogens and viruses. Developing an efficient extraction process is critical as the step determines recombinant protein concentration and purity, quantity of impurities, and process volume. Therefore, the effect of pH and time on the extraction and stability of rHSA was evaluated. The amount of rHSA in clarified extracts increased with pH (from 0.9 mg/g at pH 3.5 to 9.6 mg/g at pH 6.0) but not over time and the total soluble protein in extracts also increased with pH (from 3.9 mg/g to 19.7 mg/g). Extraction conditions that maximized rHSA purity were not optimal for rHSA stability as pH 3.5 extraction resulted in high purity (78%) but degraded over time by 56%. Similar purities were observed in pH 4.0 extracts yet rHSA remained stable. rHSA degradation was not observed in pH 4.5 and 6.0 extracts but higher native protein concentrations decreased purity which would increase purification requirements. Strategies such as pH and temperature adjustment were effective for reducing rHSA degradation in pH 3.5 rice extracts. Low temperature, pH 3.5 extraction retained high purity (97%) and stability but required higher energy inputs to maintain the low temperature. The effect of extraction conditions on subsequent purification using ion exchange chromatography (IEX) was evaluated using batch adsorption and dynamic binding capacity studies. Batch adsorption was performed to identify binding conditions that maximize rHSA adsorption and to evaluate the impact of extraction conditions on adsorption kinetics using Q SepharoseTM FastFlow® resin. A residence time of 5 min was determined to be sufficient for rHSA adsorption. Acetate and citrate (pH adjusted with TRIS), and phosphate buffers were tested for rHSA binding studies at pH 8.0. Acetate buffer was selected to maintain low conductivities and implemented during extraction to minimize processing operations and cost. The rHSA saturation binding capacities in pH 4.0, 4.5, and 6.0 extracts adjusted to pH 8.0 varied from 69 mg rHSA/mL resin (pH 4.5 extract adjusted to 8.0) to 79 mg rHSA/mL resin (pH 4.0 extracted adjusted to 8.0). Purification studies were then completed at 10% binding capacity to evaluate resultant rHSA purities and yields by using Blue SepharoseTM High Performance affinity resin. Purity and yield also varied with extraction pH with pH 4.5 extract providing an IEX fraction with the most desirable results (>95% purity and 76% yield).
Keywords: Transgenic plants; Recombinant proteins; Downstream processing; Protein extraction; Protein purification; Human serum albumin